2020
DOI: 10.1021/acsanm.9b02198
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Covalent Organic Frameworks and Surfactants to Promote Water-Based Lubrication and Corrosion Resistance

Abstract: Corrosion and friction undulation caused by waterlubricated mechanical devices severely restricts the development of water-based lubricant in practical industries. In this paper, a kind of triazine-based covalent organic framework (TriC) nanomaterial is fabricated as the water-based lubricant additive, and two kinds of surfactant, namely, coconut diethanol amide (CDEA) and Tween 85 (T-85), were chosen carefully as water-based modifiers, respectively. Then, friction behaviors were evaluated using both composite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…As reported somewhere, appropriate wettability is a prerequisite to form effective and adhesive lubricating film on a metal surface where a friction pair can be restricted from direct contact [11,33]. Wettability is generally evaluated by the magnitude of contact angle (CA), and a smaller CA implies better wettability [34].…”
Section: Wettability and Thermal Conductivitymentioning
confidence: 99%
See 1 more Smart Citation
“…As reported somewhere, appropriate wettability is a prerequisite to form effective and adhesive lubricating film on a metal surface where a friction pair can be restricted from direct contact [11,33]. Wettability is generally evaluated by the magnitude of contact angle (CA), and a smaller CA implies better wettability [34].…”
Section: Wettability and Thermal Conductivitymentioning
confidence: 99%
“…Nevertheless, its corrosive properties and poor viscosity restrain it from being used in most engineering applications. In order to improve the lubrication performance of water, recent research has been devoted to using various nanomaterials as nanoadditives dispersed in water [11][12][13][14][15][16]. These nanoadditives contribute to enhancing friction-reduction, anti-wear and load-carrying capacities of base water to a large extent, which shows great potential to be applied in hot steel rolling.…”
Section: Introductionmentioning
confidence: 99%
“…Coconut diethanol amide (CDEA) and Tween 85 (T-85) are triazine-based covalent organic framework nanomaterial (TriC) that work as additives for WBLs [86]. The wettability test used to observe the contact angle was found by placing droplets on a steel disk that were then recorded using an optical contact angle goniometer [86]. Pure water was found to be 73.3 • , while the CDEA and T-85 were 26.5 • and 58.6 • , respectively [86].…”
Section: Wettabilitymentioning
confidence: 99%
“…The results showed that the nanofluid with SDS had 4-5 days stability while without SDS the NPs agglomerated within 1 h after preparation. [116], polydopamine (PDA) [118], sodium dodecyl sulfate (SDS) [124,125], polyvinylpyrrolidone (PVP) [119], Igepal CO-520 [117], cetrimonium bromide (CTAB), and sodium dodecylbenzene sulfonate (SDBS) [119,184] Others dialkyl polyoxyethylene glycol thiophosphate ester (DTP-10, DTP-20) [154], oleylamine [93] benzalkonium chloride [90], sodium polyacrylate (PAAS) [159], SHMP (sodium hexametaphosphate), 1,4-butylene glycol [203], coconut diethanol amide (CDEA) [204]…”
Section: Surfactant Additionmentioning
confidence: 99%